Assessment of teaching curriculum in anaesthesiology for undergraduate medical students- A questionnaire based cross sectional study - Thangavelu, Swarnalingam; Malarvizhi, A.C.; Ahmed M, Nazir (International Journal of Medical Research and Review, 2016)
Background of the study:The life- saving skills like airway management,artificial ventilation, establishing an intravenous access along with fluid management and oxygen therapy devices are clearly taught by fellow Anesthesiologists in a simple manner to theundergraduate medical students. As a medical teacher it is very important to assess the students’ fund of knowledge, procedural skills, interest in learning and systems based approach in a periodical manner. Aim and objectives:To establish the insight about Anesthesiology to theundergraduate medical students and periodical assessment at the end of clinical posting. Materials and methods: The second part of III MBBS students (a total of 99 students) were enrolled in our study. A formulated teaching module was followed during their posting in our Anesthesiology department. At the end of clinical posting feedback was obtained from the students using questionnaire consisting of six questions. The data were analyzed using appropriate statistical methods Results:All the students who were enrolled in our study responded that the posting was interesting. 85% of students have told the practicaldemonstration was adequate and gave an insight into the subject of anesthesiology. 50% of the students felt that the period of posting was inadequate. 22 students gave some suggestions to improve our teaching curriculum. The top most suggestions from our study were extended duration of posting and more practical demonstration with hands on training.